A study of student's ratings of teaching effectiveness in four selected secondary schools, 1976-1977 - Misola, Aleth C. (Animo Repository, 1978)
The study seeks to interpret the ratings of teaching effectiveness of teachers in four selected secondary schools (Botolan High School, Saint Mary's Academy, Saint Theresa's College and Saint Anthony's High School) as perceived by their respective students. The rating of effectiveness concerns teachers in English, Math and Science subjects using as criteria the categorized qualities of ideal teaching behavior in the questionnaire. The evaluation instrument used was based on the original Teacher Behavior Inventory (TBI) by Kendal Tang (1975). The Survey of Teaching Effectiveness (STE) consists of 50 evaluated statements grouped into four categories. The study is based on an underlying assumption of the teacher-learner relationships. The author intended to answer the question: What will be revealed by students' perception of their teachers?